2017
DOI: 10.1515/chem-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temporary seasonal variation of heavy metals and their potential ecological risk in Nzhelele River, South Africa

Abstract: Surface water is often used as alternative source of drinking water in many regions of the world where the potable water supply is erratic or not present. The concentration of heavy metals was assessed using an Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). The impact of temporary seasonal variation on the contamination level was also assessed. Contamination factor (CF) and Hakanson's potential ecological risk (E r and RI) indices were used to evaluate the toxicity levels of the metals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The key environmental drivers across the wet and dry seasons include: volume of water, flow, frequency of rainfall events, storm run-off, evaporation and point sources of pollution [35,36]. An increase in storm-water run-off within a river catchment may increase the level of contaminants due to land-use activities.…”
Section: Introductionmentioning
confidence: 99%
“…The key environmental drivers across the wet and dry seasons include: volume of water, flow, frequency of rainfall events, storm run-off, evaporation and point sources of pollution [35,36]. An increase in storm-water run-off within a river catchment may increase the level of contaminants due to land-use activities.…”
Section: Introductionmentioning
confidence: 99%
“…This index takes into account the preindustrial reference level of metals of concern. Worldwide this ecological RI was found to be useful in assessing the pollution risk of soils and sediments in both the terrestrial and the marine environments . One of the weaknesses of the Hakanson index is that it does not take into account the lithogenic and sedimentary inputs.…”
Section: Methodsmentioning
confidence: 99%
“…The Nzhelele River originates from Soutpansberg Mountains, meanders past rural communities, and flows past Nzhelele dam northwards into the Limpopo River. The sources of metal pollution are Siloam and Makhado oxidation ponds which discharge their effluent into the Nzhelele River [21,22]. The area is characterized by urban settlements of Biaba and residential houses, some with pit latrines, subsistence and commercial farming and nature reserves.…”
Section: Characteristics Of the Study Areamentioning
confidence: 99%
“…The presence of Al was attributed in part due to discharge of sewage effluent into the Groot Nyl River, a subtributary of the Nyl River, and rainfall-induced erosion of local bedrock. The study by Edokpayi et al [19,21,24] showed variation in the Al level in the Ga-Selati, Nzhelele, Mvudi, and Dzindi Rivers in excess of the target water-quality range. The high level of Al may be attributed to the Thohoyandou sewage plant which discharges treated effluent into the Mvudi River and Vuwani oxidation ponds which discharge into Dzindi River [19,20,29].…”
Section: Aluminum (Al)mentioning
confidence: 99%